Gendered educational leadership: beneath the monoglossic façade - Fuller, Kay (Taylor & Francis, 2014)
Recent gender retheorisation has drawn on Mikhail Bakhtin's literary and linguistic theories of monoglossia and heteroglossia to reconcile seemingly contradictory gender discourses. Thus, girls/women and boys/men as they are biologically sexed might be discussed within a poststructural gender theory discourse that disconnects gender from the body. The concepts of gender monoglossia, gender heteroglossia and polyglossia have been applied here to empirical research into the construction of gendered leadership as it was seen to be done by one woman head teacher. The accounts of members of staff expose heteroglossia in the articulation of their understandings of gendered leadership beneath the construction of a monoglossic façade. They also reveal an understanding of polyglossic simultaneity as the head teacher is observed to ‘switch’ seamlessly between modes of doing gendered leadership depending on context and circumstances. There is also evidence of polyglossic simultaneity in the reports that might lead to the rejection and/or redefinition of gender theory discourses.